Thirty years of American cave diving fatalities - Potts, L.; Buzzacott, Peter; Denoble, P. (2016)
INTRODUCTION: Cave divers enter an inherently dangerous environment that often includes little visibility, maze-like passageways and a ceiling of rock that prevents a direct ascent to the surface in the event of a problem.METHODS: Reports of cave diving fatality cases occurring between 01 July 1985 and 30 June 2015 collected by Divers Alert Network were reviewed. Training status, safety rules violated, relevancy of the violations, and root causes leading to death were determined.RESULTS: A total of 161 divers who died were identified, 67 trained cave divers and 87 untrained. While the annual number of cave diving fatalities has steadily fallen over the last three decades, from eight to less than three, the proportion of trained divers among those fatalities has doubled. Data regarding trained cave divers were divided into two equal 15-year time periods. Trained cave divers who died in the most recent time period were older but little else differed. The most common cause of death was asphyxia due to drowning, preceded by running out of breathing gas, usually after getting lost owing to a loss of visibility caused by suspended silt. An overwhelming majority of the fatalities occurred in the state of Florida where many flooded caves are located.CONCLUSION: Even with improvements in technology, the greatest hazards faced by cave divers remain unchanged. Efforts to develop preventative interventions to address these hazards should continue.